Loss to follow-up and associated factors among adult people living with HIV at public health facilities in Wakiso district, Uganda: a retrospective cohort study - Opio, Denis; Semitala, Fred C.; Kakeeto, Alex; Sendaula, Emmanuel; Okimat, Paul; Nakafeero, Brenda; Nankabirwa, Joaniter I.; Karamagi, Charles; Kalyango, Joan N. (BMC health services research, 2019)
Loss to follow-up (LTFU) from care among people living with HIV (PLHIV) is thought to be more common in the public setting compared to the private health care. It is anticipated that the problem may become worse with the current “test and treat” policy in Uganda due to the likely increases in patient loads and its attendant pressure on health care providers to support patient counseling. This study determined the incidence and factors associated with LTFU from HIV care among adult PLHIV in public health facilities in Wakiso district, Uganda. Methods: This was a retrospective cohort study that involved the review of 646 records of patients initiated on antiretroviral therapy (ART) between January 1st, 2015 and December 31st, 2017 at 13 randomly selected public health facilities in Wakiso district. The cox proportional hazards regression was used to determine the factors associated with LTFU. The results were supported by sequential in-depth and key informant interviews to explore reasons for LTFU. Results: Of the 646 patients enrolled, 391 were female (60.5%), 282 were below 30 years (43.6%) and 207 were married (50.1%). A total of 216 patients (33.4%) had no documented outcomes and were considered LTFU. The incidence of LTFU was 21 per 1000 person months (95% confidence interval (CI): 18–25 per 1000 person months). Factors associated with LTFU included having normal weight compared to underweight (adjusted hazard ratio (aHR) 0.64, 95% CI: 0.45–0.90, p = 0.011), receiving HIV care from hospitals compared to lower level facilities (aHR 0.22, 95% CI: 0.12–0.41, p < 0.001), and no telephone contact compared to those with a telephone contact (aHR 2.16, 95% CI: 1.33–3.51, p = 0.002). Stigmatization and long waiting times were the prominent reasons for LTFU reported from the in-depth and key informant interviews. Conclusions: The incidence of LTFU in public health facilities in Uganda is quite high and is associated with being underweight, not having a telephone contact to receive reminders and receiving care at lower level facilities. Early diagnosis, routine use of patient address locator forms and improved quality of HIV care at lower level health facilities may reduce LTFU among PLHIV.
Keywords: Loss to follow-up; HIV care; PLHIV; Public health facilities